Analysis of the operational characteristics of a high-Tc superconducting power supply with the Bi-2223 pancake load. - Yoong Soo Yoon
This paper presents the design and fabrication of a high-Tc superconducting (HTSC) power supply with the Bi-2223 pancake load, as well as its characteristics as determined through experiments. HTSC power supply consists of two heaters, an electromagnet, a Bi-2223 solenoid, and a Bi-2223 pancake load. In this experiment, a 331-mH electromagnet and 0.8-A dc heater current were used, and 8.5 and 17 s were used for pumping periods, respectively. Mechanism of the superconducting switch is used for heater-trigger. In order to measure the pumping-current with respect to the magnet flux changes, a hall sensor was installed at the center of the Bi-2223 pancake load. The experimental observations have been compared with the theoretical predictions. In this experiment, the pumping-current has reached about 0.6 A with 0.01-V electromagnet voltage.
Keywords: Bi-2223 pancake load; Bi-2223 solenoid; Hall sensor; Electromagnet; Heater-trigger.; High-Tc superconducting power supply; Magnetic flux; Pumping current; Superconducting switch; Bi2Sr2Ca2Cu3O.